Friction stir surfacing of cast A356 aluminium–silicon alloy with boron carbide and molybdenum disulphide powders - R. Srinivasu; A. Sambasiva Rao; G. Madhusudhan Reddy; K. Srinivasa Rao (Defence Technology, 2015)
Good castability and high strength properties of Al–Si alloys are useful in defence applications like torpedoes, manufacture of Missile bodies, and parts of automobile such as engine cylinders and pistons. Poor wear resistance of the alloys is major limitation for their use. Friction stir processing (FSP) is a recognized surfacing technique as it overcomes the problems of fusion route surface modification methods. Keeping in view of the requirement of improving wear resistance of cast aluminium–silicon alloy, friction stir processing was attempted for surface modification with boron carbide (B4C) and molybdenum disulfide (MoS2) powders. Metallography, micro compositional analysis, hardness and pin-on-disc wear testing were used for characterizing the surface composite coating. Microscopic study revealed breaking of coarse silicon needles and uniformly distributed carbides in the A356 alloy matrix after FSP. Improvement and uniformity in hardness was obtained in surface composite layer. Higher wear resistance was achieved in friction stir processed coating with carbide powders. Addition of solid lubricant MoS2 powder was found to improve wear resistance of the base metal significantly.